TINJAUAN YURIDIS HARMONISASI PERLINDUNGAN DATA PRIBADI E-CONSUMER PADA KEGIATAN JUAL BELI DALAM PLATFORM ONLINE MARKETPLACE - Disty Allyagita Cahyani; Anjar Sri Ciptorukmi Nugraheni (Jurnal Privat Law, 2025)
AbstractThis  article  examines  the  laws  and  regulations  of  e-consumer  personal  data protection in buying activities in online marketplace, also the harmonization of these  regulations  with  the  personal  data  protection  bill.  This  research  is  a prescriptive normative with statutory approach. The data used were primary data and secondary data. Data collection techniques carried out by literature study or document study with qualitative deductive legal material analysis techniques. The results of the reseacrh and discussion show that the laws and regulations in Indonesia have regulated the protection of e-consumer personal data in online marketplace platform, but are still scattered in several laws and regulations. Meanwhile, the personal data protection bill regulates the protection of personal data  in  general,  not  only in  the scope  of  systems  or  electronic transactions. Harmonization   between   the   personal   data   protection   bill   and   laws   and regulations has been implemented in several aspects, includes the obligations of users of personal data, the rights of the owner of personal data, to role of the government and society. Where the personal data protection bill regulates in more detail or clarifies what has been regulates in laws and regulations. Keywords:  E-Consumer;  Harmonization;  Online  Marketplace;  Personal  Data ProtectionAbstrakArtikel ini mengkaji bentuk perlindungan data pribadi e-consumer dalam kegiatan jual beli online marketplace dalam peraturan perundangan-undangan serta harmonisasi peraturan tersebut dengan Rancangan Undang-Undang Perlindungan Data Pribadi. Penelitian ini adalah penelitian hukum normatif yang bersifat preskriptif   dengan   pendekatan   perundang-undangan.   Bahan   hukum   yang digunakan adalah bahan hukum primer dan bahan hukum skunder. Teknik pengumpulan  data  dilakukan  dengan  studi  kepustakaan  atau  studi  dokumen, dengan teknik analisis bahan hukum bersifat deduktif kualitatif. Hasil penelitian dan   pembahasan   menunjukkan   bahwa   peraturan   perundang-undangan   di Indonesia telah mengatur perlindungan data pribadi e-consumer dalam platform online marketplace, namun masih tersebar di beberapa peraturan perundang- undangan. Sedangkan untuk RUU PDP mengatur perlindungan data pribadi secara umum tidak hanya di lingkup sistem atau transaksi elektronik. Harmonisasi antara Rancangan Undang-Undang Perlindungan Data Pribadi dan peraturan perundang- undangan telah terlaksana dalam beberapa aspek, mencakup kewajiban pengguna data pribadi, larangan-larangan terhadap data pribadi, hak pemilik data pribadi, hingga peran dari pemerintah dan masyarakat. Dimana Rancangan Undang- Undang Perlindungan Data Pribadi mengatur lebih terperinci atau memperjelas kembali yang sudah diatur dalam peraturan perundang-undangan.Kata Kunci: E-Consumer; Harmonisasi; Online Marketplace; Perlindungan DataPribadi